Enhancing Students’ Ability in Extending Ideas in the Narrative Writing through the 5W1H Concept - Shabir, M. (ENGLISH JOURNAL, 2016)
This study sought to investigate the result of implementing 5W1H concept in enhancing students’ ability in writing composition especially the narrative type at Al-Ijtihad Islamic Boarding School located in Bogor, West Java. The study started with an introductory session regarding the 5W1H concept which is so far only known in the newspaper writing. The data used to analyze the study was the texts of narrative made by students before and after the treatment was given. The result of the study indicates that implementing the journalistic concept helps the students develop significantly their ideas in writing as shown by significant progress made by each student after the treatment. At the end of this study, some conclusions and weaknesses of the study are made for a better strategy in teaching narrative writing for the students.